2019
DOI: 10.1021/acsanm.9b02286
|View full text |Cite
|
Sign up to set email alerts
|

Ionophore-Based Ion-Selective Nanosensors from Brush Block Copolymer Nanodots

Abstract: The selectivity of ionophore-based sensors is crucial to real applications such as clinical diagnostics and bioimaging. Previous ion-selective nanosensors developed from amphiphilic block copolymers are attractive because of simple fabrication, high stability, and versatility. However, the selectivity was reduced compared with polymeric ion-selective membranes. Here, we present ionophore-based nanosensors from graft copolymer nanodots (23.5 ± 3.8 nm in diameter) with significantly improved selectivity and exce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 48 publications
1
17
0
Order By: Relevance
“…Figure 1b shows a transmission electron microscopy (TEM) image that shows an average diameter around 50 nm, which agrees well with the previously reported nanospheres formed with similar materials. 43 According to the literature, cyanine dyes tend to form Jaggregation or H-aggregation, 44,45 and, in particular, strong Haggregation could occur in aqueous solutions. 46 DTTC has been demonstrated to form dimer in aqueous solutions, 47 which is accompanied by blue-shifted absorption.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Figure 1b shows a transmission electron microscopy (TEM) image that shows an average diameter around 50 nm, which agrees well with the previously reported nanospheres formed with similar materials. 43 According to the literature, cyanine dyes tend to form Jaggregation or H-aggregation, 44,45 and, in particular, strong Haggregation could occur in aqueous solutions. 46 DTTC has been demonstrated to form dimer in aqueous solutions, 47 which is accompanied by blue-shifted absorption.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…While large LipiSensors can be used for extracellular and in vivo applications, the small sensors can be used for small intracellular compartments to detect the compartmentalization of Ca +2 , transmembrane Ca +2 dynamics, and potentially aiding in characterization of Ca +2 flux from organelles to the cytoplasmic space (and vice versa) [ 43 , 46 , 47 ]. The small LipiSensors in this work are ~120 nm in diameter, but it may be possible to formulate much smaller sizes, as other groups have shown Lipidots with 25 nm [ 28 ] and IBNS with 20 nm diameters [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, this structural support function should also work with other materials while maintaining the sensing mechanism as long as the material properties are similar. The fundamental mechanism of IBNS has been demonstrated in a wide range of supporting matrices and is not impacted [ 22 , 23 , 24 , 25 ], as others have demonstrated that it is possible to make sensors with only plasticizer [ 24 ], brush block copolymers [ 27 ], surfactant alone [ 23 ], and even SiO 2 nanoparticles [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The system was used for the perception of heptanal as a lung cancer biomarker in human blood [ 94 ]. Along with the analysis of cancer biomarkers, electrochemical MSAs can be applied for blood screening for the biomarkers of hypertension [ 95 ], cardiovascular disease [ 96 , 97 ], for evaluation of the concentration of purine nucleotides [ 98 ], metal ions [ 99 ], urea, creatinine and uric acid [ 100 ], etc.…”
Section: Application Of Msss and Msasmentioning
confidence: 99%